The Gantangan Tradition and Normative Bias: a Socio-Cultural Study of the Sundanese Community - Mohammad Fadli Alvarizi Fadli; Fitria Novianti; Iip Miftahul Janah; Nailah Chayara Alima; Ruhaliah; Zulfikar Alamsyah (Pusat Studi Wanita dan Keluarga UGM, 2026)
This study examines gantangan, a reciprocal social practice in Sundanese culture involving the exchange of money, food, or labor with a strict obligation for future reciprocation. Utilizing a systematic literature review and conceptual analysis, the research investigates this tradition through the lens of normative bias—the tendency to conform to both injunctive and descriptive social norms. The findings reveal that gantangan is a structured social system driven by six key psychological factors: injunctive norm pressure, reciprocal obligation, shame, descriptive norm ambiguity, communal identity threat, and cognitive dissonance. Psychologically, participation is primarily motivated by external conformity rather than genuine intrinsic sincerity. This behavioral pattern is further reinforced by commitment escalation and post-hoc rationalization. While gantangan functions effectively as a solidarity bond and a community financial safety net, it simultaneously diminishes individual autonomy and imposes disproportionate financial burdens. The article concludes that a meaningful reinterpretation of gantangan is essential to preserve its cultural essence while ensuring it does not evolve into a source of oppressive normative pressure that burdens the community.